Efficient production of cellooligosaccharides and xylooligosaccharides by combined biological pretreatment and enzymatic hydrolysis process - Felipuci, Jefferson Poles; De Freitas, Caroline; Sanches, Alex Otávio [UNESP]; Grillo, Renato [UNESP]; Attili-Angelis, Derlene; Brienzo, Michel [UNESP] (Springer, 2024)
Xylooligosaccharide and cellooligosaccharide production has been improved over the years using different kinds of methods. Chemical and physical methods are the most used due to their facility in reducing the biomass recalcitrance; however, such methods require a great deal of energy and generate undesirable compounds. On the other hand, biological pretreatment is an option to overcome the high energy demand and pollution issues and optimize production. In this work, sugarcane bagasse was biologically pretreated with Coniophora puteana (CBMAI 0870), Gloeophyllum trabeum (CBMAI 0872), and Pleurotus ostreatus (CCIBt 2338) for 5 months. After the biological pretreatment, part of the material was milled in a knife mill (20-mesh) and another part was milled in a ball mill (powder aspect). The material was enzymatic hydrolyzed with cellulase (20, 50, and 100 IU/g) and xylanase (50 IU/g) combined with the milling techniques to produce cellooligosaccharides and xylooligosaccharides. Xylooligosaccharides and cellooligosaccharides were characterized by ATR-FTIR analysis, scanning electron microscopy images and X-ray to evaluate the modifications in the lignocellulosic structure. The enzymatic hydrolysis using cellulase (50 IU/g) combined with knife milling resulted in 26.23% of cellooligosaccharide conversion after 5 months of cultivation with C. puteana, while cellulase with the same enzymatic charge combined with ball milling resulted in 36.65% of cellooligosaccharide conversion using the same fungus and the same time of cultivation. Xylooligosaccharide conversion also reached better results when compared to untreated material: the best result was 78.12% of xylooligosaccharide conversion after the biological pretreatment with G. trabeum. Finally, scanning electron microscope images made it possible to observe gaps formed by the fungi growth in the biomass in comparison to untreated material; and x-ray analysis showed evidence of the effect of ball milling pretreatment in the biomass, reducing its crystallinity.
Produção eficiente de celooligossacarídeos e xilooligossacarídeos por pré-tratamento biológico combinado e processo de hidrólise enzimática
Keywords: Ball mill; Biomass recalcitrance